A MOTIVATION AND IMAGE OF WOMEN WITH DISABILITIES IN THE NOVEL "SARASWATI SI GADIS DI SUNYI" BY A.A NAVIS: A STUDY OF LITERARY PSYCHOLOGY : Abstrak - Qurrota Ayu Neina (Abjad Journal of Humanities & Education, 2023)
The rise of acts of concern for women, especially those with disabilities, has resulted in a loss of enthusiasm and hope for women with disabilities who want to work and develop their capabilities. This study aimed to describe the analysis of the motivation and image of women with disabilities in the study of literary psychology. The object of this study was an academic work in the form of a novel entitled "Saraswati Si Gadis dalam Sunyi" by A. A. Navis. The approach used in this study was qualitative descriptive with a content analysis research design. The research instrument in this study was data from the authors' content analysis with the help of tables to facilitate analysis. The results of this study showed that there were 39 motivational elements and 29 images of women with disabilities. Through this study, it is hoped that the community can better appreciate the existence of women with disabilities and support their activities to improve their capabilities.